Perplexed by PGx? Exploring the impact of pharmacogenomic results on medical management, disclosures and patient behavior. (15th April 2019) - Waldman, Larissa; Shuman, Cheryl; Cohn, Iris; Kaiser, Amy; Chitayat, David; Wasim, Syed; Hazell, Allison
Pharmacogenomic (PGx) tests represent significant advances in precision medicine. Our aim was to explore perceptions following the return of PGx results, medication management, and disclosure to providers. We surveyed clients who had PGx testing and conducted a chart review of PGx results. Respectively, 84% and 94% of participants found pre- and post-test genetic counseling helpful. There was a significant difference in disclosure, while 6% disclosed results to a pharmacist, 50% disclosed to a physician. Qualitative analysis identified three themes: 1) psychological response; 2) perceived utility; 3) experiences with disclosure. Our study supports the provision of genetic counseling for a non-disease related genetic test. Benefits of PGx testing can be optimized by the collaboration of physicians, pharmacists, genetic counselors and patients.